High-Performance Mobility Simulation: Implementation of a Parallel Distributed Message-Passing Algorithm for MATSim - Janek Laudan; Paul Heinrich; Kai Nagel (Information)
Striving for better simulation results, transport planners want to simulate larger domains with increased levels of detail. Achieving fast execution times for these complex traffic simulations requires the parallel computing power of modern hardware. This paper presents an architectural update to the MATSim traffic simulation framework, introducing a prototype that adapts the existing traffic flow model to a distributed parallel algorithm. The prototype is capable of scaling across multiple compute nodes, utilizing the parallel computing power of modern hardware. Benchmarking reveals a 119-fold improvement in execution speed over the current implementation, and a 43 times speedup when compared to single-core performance. The prototype can simulate 24 h of large-scale traffic in just 3.5 s. Based on these results, we advocate for integrating a distributed simulation approach into MATSim and outline steps for further optimizing the prototype for large-scale applications.